Edukasi Pentingnya Konsumsi Tablet Tambah Darah pada Remaja di MAN 2 Kota Banjarmasin - Mi'rajunnisa; Nur Lathiifah (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
Anemia remains a health problem among adolescents, especially adolescent girls, partly due to low knowledge and compliance with Iron Supplement Tablets (IST). This community service activity aims to increase students' knowledge about anemia and the importance of consuming IST through health education interventions. The activity was carried out at MAN 2 Banjarmasin with a pre-test and post-test design, involving 35 students selected purposively. The intervention was delivered in the form of lectures, PowerPoint presentations, and leaflets containing information about anemia, risks in adolescents, and how to consume TTD. The pre-test results showed that most students were in the low knowledge category (57%), while only 14% were in the good category. After the intervention, the post-test results showed a significant increase, with 94% of students in the good knowledge category and no students in the poor knowledge category. Improvements were also seen in all question indicators, such as understanding of anemia, which increased from 34% to 97%, and knowledge of TTD consumption times, which increased from 20% to 80%. This activity shows that health education through lectures, PowerPoint presentations, and leaflets is ef ective in increasing students' knowledge about anemia and TTD consumption, thereby potentially supporting ef orts to prevent anemia in school-age adolescents.